The importance of cooperative learning for deaf and hard-of-hearing students in informal educational contexts - Kordić, Milena; Karić, Jasmina (Specijalna edukacija i rehabilitacija, 2023)
Introduction. This paper aims to present the most adequate conditions and access for the learning and development of deaf and hard-of-hearing students. By applying the cooperative learning model in informal educational contexts, interactions between students are enhanced within spaces that allow these interactions to take place more freely and dynamically. In these conditions, student socialization becomes more successful, and contextual and experiential learning is also encouraged, which contributes to the acquisition of permanent and functional knowledge. Objective. The aim of the paper was to analyze the available literature from 2000 to 2022 to highlight the advantages of applying cooperative learning in informal educational contexts in the education of deaf and hard-of-hearing students. Method. The following search engines were used for the literature search: Ebscohost, ScienceDirect, KoBSON, and Google Scholar. Results. In informal educational contexts, the entire perceptive sensory experiences of deaf and hard-of-hearing students, despite the hearing impairment, gain importance, come to life, and are enriched in a system of knowledge and skills that will help them understand the world around them and find their way in it. Cooperative learning has produced positive results in the development of communication skills and academic achievement of deaf and hard-of-hearing students. Its application through informal educational contexts would lead to effective learning and successful socialization. Conclusion. In addition to the development of cognitive and social abilities, interactions created with the help of cooperative learning in informal contexts can contribute to the essential realization of the inclusion of deaf and hard-of-hearing students, both in education and society.
Keywords: informal educational contexts; cooperative learning; deaf and hard-of-hearing students